FAILURE ANALYSIS OF HIGH STRENGTH ALUMINUM ALLOY WHEEL - YU JianMin; ZHANG ZhiMin; WANG Qiang (Jixie qiangdu)
The mechanism of cracks initiation and propagation of high strength aluminum alloy rims for heavy vehicles were analyzed. Tensile testing machine,optical microscopy,scanning electronic microscope and energy disperse spectrometer detailed characterization of the mechanical properties,fracture morphology,crack characteristics and corrosion products of aluminum alloy wheel respectively. The results show that the crack is look like the shape"Z",expanding along the grain boundary and fracture;there are corrosive elements Cl and S at the crack initiation zone and crack extension area,with characteristics of typical stress corrosion. According to the actual assembly and service condition,it exist electric potential difference between aluminum alloy wheel and steel lock ring under the condition of corrosive medium,which will generate galvanic corrosion. After T6 heat treatment,there areηphase,S phase and θ phase on the grain boundary of 7 A04 aluminum alloy. In the corrosion environment,the matrix grain priority to dissolute itself as anodic,which makes the grain boundary become active path,crack propagation along the path lead to fracture.